Reaction of 2,6-dichloroquinone-4-chloroimide (Gibbs reagent) with permethrin - an optical sensor for rapid detection of permethrin in treated wood - Arip M.N.M.; Heng L.Y.; Ahmad M.; Hasbullah S.A. (2024)
Background: A novel optical sensor for the rapid and direct determination of permethrin preservatives in treated wood was designed. The optical sensor was fabricated from the immobilisation of 2,6-dichloro-p-benzoquinone-4-chloroimide (Gibbs reagent) in nafion/sol-gel hybrid film and the mode of detection was based on absorption spectrophotometry. Physical entrapment was employed as a method of immobilisation.Results: The sensor gave a linear response range of permethrin between 2.56-383.00 ?M with detection limit of 2.5 ?M and demonstrated good repeatability with relative standard deviation (RSD) for 10 ?M at 5.3%, 100 ?M at 2.7%, and 200 ?M at 1.8%. The response time of the sensor was 40 s with an optimum response at pH 11.Conclusions: The sensor was useful for rapid screening of wood or treated wood products before detailed analysis using tedious procedure is performed. The validation study of the optical sensor against standard method HPLC successfully showed that the permethrin sensor tended to overestimate the permethrin concentration determined. 2013 Arip et al.; licensee Chemistry Central Ltd.